Oxidation of soot in gasoline exhaust on Mn2O3 catalyst - Singer, Christian; Hahn, Christoph; Phan, Dai Q.; Russwurm, Tim; Wensing, Michael; Koegl, Matthias; Zigan, Lars; Kureti, Sven (Applied Catalysis A-General, 2023)
A Mn2O3 catalyst was investigated for soot oxidation in gasoline exhaust. Catalytic studies performed in model exhaust with Mn2O3/soot mixtures in tight contact showed efficient soot oxidation above 250 °C. This high performance was additionally confirmed on a gasoline engine test bench using a Mn2O3-coated particulate filter. The mechanism of the oxygen transport from the gas phase to soot was investigated by kinetic modeling of O2 adsorption and desorption as well as catalytic studies using 18O2. As a result, it was suggested that O2 dissociatively adsorbs on Mn2O3 followed by surface migration and transfer of oxygen to the soot at physical contact points between the two solids. The surface, sub-surface and bulk oxygen of the catalyst were also found to play a role. Enhanced participation of bulk oxygen appeared with declining O2 content due to partial reduction of Mn2O3 and formation of oxygen vacancies driving the oxygen mobility.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Gasoline exhaust; Isotopic labeling; Mechanism; Mn; Soot oxidation